The Effect of Nickel Mining on Acute Respiratory Infection Cases in Boenaga Village, Lasolo District, North Konawe Regency - Ginting, Elfrina; Supodo, Timbul; Sunarsih, Sunarsih; Ayu Sudirman, Putri; Reinaldy Juliansyah, Muhammad (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: Nickel mining industry with air with nickel dust and combu stion gases. The main effects of dust on workers are either acute lung disorders or chronic physiological disorders, eye irritation, sensory irritation, and accumulation of harmful substances in the body. One of the negative impacts of nickel processing activities is environmental degradation which is characterized by air and many diseases related to the respiratory tract. This greatly affects the people who live close to mining areas, based on data from the Lasolo Island Health Center shows that ARI cases in 2020 were 126 cases, Asthma 85 cases, and Toddler Pneumonia 23 cases. The purpose of this study was to determine the effect of mining on cases of ARI in mining areas in the village of Boenaga. Method: The type of research used in this study is an observational study with a cross sectional analytic study. Result: The results showed that there was a relationship between dust exposure and cases of respiratory disease. Conclusion: The condition of indoor and outdoor air quality in exposed areas was higher than in non-exposed areas, but all of these are still below the permissible threshold value. The incidence of ARI in exposed locations increased significantly compared to non-exposed locations in Pomalaa district.